Effect of cavity-cleaning agents on shear bond strength between self-etching adhesives and dentin - Tamiris Alacoque de Carvalho Freitas; Bruno Salles Sotto-Maior; Mariele Ferraz de Oliveira; Fabiana Cesar Costa; Luciana Andrea Salvio (Universidade Estadual de Campinas, 2019)
Aim: The effect of cavity-cleaning agents on shear bonding strength between self-etching adhesives and dentin was evaluated. Methods: Twenty-five healthy human third molars were worn to obtain flat middle dentin. The samples were randomly divided into five groups according to the cleaning agent used: group CB not treated with any cavity disinfectants and served as control. Following groups, dentin surfaces were treated with 2% chlorhexidine (CHX group); 3% hydrogen peroxide (HP group); calcium hydroxide water (CH group); and 70% ethyl ethanol (E group). The dentin surfaces were cleaned by friction for 20 s and dentine bonding agent, Clearfil SE Bond, was applied. Cylinders (5.0 mm  1.2 mm, n = 19) of fluid composite resin were placed on the dentin surface, and the teeth were stored in deionized water at 37°C for 24 h. Subsequently, the samples were subjected to the shear bonding test, and the obtained values were subjected to one-way ANOVA and Tukey's test (α = 0.05). The failure pattern was analyzed descriptively by examining the specimens with a stereoscope at a magnification of 4, and failure was classified into adhesive, cohesive or mixed type. Results: Shear bonding was significantly lower in group HP (6.17 ± 5.69 MPa). The groups CB, CHX, CH and E were statiscally similar, 22.15 ± 6.54MPa; 18.40 ± 7.26MPa; 18.07 ± 5.98MPa ; 16.43 ± 6.19MPa respectively. The failure modes observed were only adhesive and mixed. Conclusion: The use of 2% chlorhexidine, calcium hydroxide water, and 70% ethyl ethanol did not negatively affect bond strength. Only 3% hydrogen peroxide is contraindicated as a cavity cleaner in adhesive restorative procedures when self-etching system is used.